Average Error: 0.0 → 0.0
Time: 10.1s
Precision: 64
\[x + \left(y - x\right) \cdot t\]
\[x + \left(y - x\right) \cdot t\]
x + \left(y - x\right) \cdot t
x + \left(y - x\right) \cdot t
double f(double x, double y, double t) {
        double r1355880 = x;
        double r1355881 = y;
        double r1355882 = r1355881 - r1355880;
        double r1355883 = t;
        double r1355884 = r1355882 * r1355883;
        double r1355885 = r1355880 + r1355884;
        return r1355885;
}

double f(double x, double y, double t) {
        double r1355886 = x;
        double r1355887 = y;
        double r1355888 = r1355887 - r1355886;
        double r1355889 = t;
        double r1355890 = r1355888 * r1355889;
        double r1355891 = r1355886 + r1355890;
        return r1355891;
}

Error

Bits error versus x

Bits error versus y

Bits error versus t

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[x + \left(y - x\right) \cdot t\]
  2. Final simplification0.0

    \[\leadsto x + \left(y - x\right) \cdot t\]

Reproduce

herbie shell --seed 1 
(FPCore (x y t)
  :name "x + (y - x) * t"
  :precision binary64
  (+ x (* (- y x) t)))